On the cross road of polity, political elites and mobilization - Wejnert, Barbara; Parigi, Paolo, 1973- (Advances in motivation and achievement ;, 2016)
This volume discusses the various interrelations that exist within and between social and political phenomena. This includes exploring the underlying social roots or origins of politics and power; the organisation, management, and process of political power structure; and the effects of political decision-making and power structures on the surrounding society and culture.